Fabrication of Uniformly Arrayed Single- and Multi-Directional Slanted Cu Nanorods. (26th August 2015) - Cho, Sung-Woon; Kim, Jun-Hyun; Bak, Jeong Geun; Kim, Chang-Koo
Abstract : Uniformly arrayed single- and multi-directional slanted Cu nanorods on a Si substrate were fabricated using a template of slanted channel structures. The single-directional slanted Cu nanorods were obtained using slanted channel structures oriented at an angle of 15° with respect to the surface normal. Double- and quadruple-directional slanted Cu nanorods were obtained using double- and quadruple-directional slanted channel structures, respectively. The double-directional Cu nanorods were symmetrically slanted at 30°, preserving the architecture of the slanted channel structures. The quadruple-directional slanted Cu nanorods had pyramidal structures, with slanted rods positioned at 30° from the surface normal to the right, left, front, and back.